ANTIOXIDANT ACTIVITY OF THE HERB REMEDY AND ITS COMPONENTS IN VITRO - P. B. Lubsandorzhieva (Acta Biomedica Scientifica, 2012)
Antioxidant activity of adaptogenic remedy Adaptophyte and its components was studied. The most effective antioxidants are the components of Adaptophyte: Bergania crassifolia (L.) Fritsch, Polygonum, aviculare L., Cinnamomum. cassia which inhibit formation МDА in the least concentration (less than 100 mkg/ml). Water-soluble substances of Punica granatum. L., Myristica fragrans Houtt., Rhaponticum. сarthamoides (Willd.), Zingiber officinale Rodcoe, Calendula officinalis L. have average indexes antioxidant activity (IC50 from 100 to 500 mkg/ml). Decoctions from Althaea officinalis L., Piper longum. L., Elettaria cardamomum. Maton., Inula helenium. L., Acorus calamus L. show antioxidant activity in high concentrations.